An Expanded Dengue Syndrome Patient With Manifestation Myocarditis: Case Report - Muhammad Vitanata Arfijanto, -
Dengue infection may manifest asymptomatic, dengue fever, dengue hemorrhagic fever, dengue shock syndrome. However, atypical manifestations in other organs have been increasingly reported and called expanded dengue syndrome. One of the cardiac complications in dengue is myocarditis. An 18-year-old woman complains of high fever since 3 days, epistaxis, chest pain, dyspnea, and vomiting. Laboratory examination obtained thrombocytopenia, hemoconcentration, NS1, IgG-IgM dengue positive, CKMB and TroponinI increase. Electrocardiogram result ischemic anterior-posterior. Echocardiography results hyperechogenic on myocardial suspicious a myocarditis. The patient was diagnosed with acute myocarditis and dengue hemorrhagic fever. Condition improved after five days of treatment. Cardiac complications in dengue are now increasingly observed with the most common case is myocarditis. The main mechanism of dengue myocarditis is still unknown though both direct viral infection and immune mediated damage have been suggested to be the cause of myocardial damage. The low incidence of dengue myocarditis is because it’s asymptomatic and diagnosis is easily missed. Almost all cases of dengue myocarditis are self-limiting and severe myocarditis leading to dilated cardiomyopathy is extremely rare. There have been reported a patient with dengue hemorrhagic fever with manifestation myocarditis. Condition improve with supportive management.